Method of preparing positive electrode active material for lithium secondary battery

JP2025023056APending Publication Date: 2025-02-14ECOPRO BM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024206844
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-10-27
Filing Date
2024-11-28
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0025】 本発明によれば、正極活物質を製造する工程中に、ニッケル複合前駆体と第1添加剤を混合した後、一次熱処理することによって収得された第1リチウム複合酸化物のBET比表面積が前記ニッケル複合前駆体に対して所定の範囲内に存在するように制御し、前記第1リチウム複合酸化物と第2添加剤を混合した後、二次熱処理することによって、収得された第2リチウム複合酸化物のBET比表面積が前記第1リチウム複合酸化物に対して所定の範囲内に存在するように制御することによって、前記正極活物質に特定の金属元素をドープしたり前記正極活物質の表面にコーティング層を導入する場合にも、前記正極活物質の電気化学的特性および/または安定性が低下するのを防止することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023056000001
    Figure 2025023056000001
  • Figure 2025023056000002
    Figure 2025023056000002
Patent Text Reader

Abstract

To provide a positive electrode active material for a lithium secondary battery prepared by a method of preparing the same, which is able to improve electrochemical properties and stability of the positive electrode active material by controlling the specific surface area of the positive electrode active material.SOLUTION: A positive electrode active material comprises: a lithium composite oxide enabling intercalation / deintercalation of lithium; a first oxide layer covering at least a part of a surface of the lithium composite oxide; and a second oxide layer covering at least part of a surface of the lithium composite oxide not covered by the first oxide layer and a surface of the first oxide layer. The first and second oxide layers contain a boron-containing oxide represented by Chemical Formula 3 described in the specification. The lithium composite oxide is represented by Chemical Formula 1 described in the specification.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery, and more specifically, to a method for producing a positive electrode active material for a lithium secondary battery that can improve electrochemical characteristics and stability by controlling the specific surface area of ​​the positive electrode active material. [Background technology]

[0002] Batteries store electricity by using materials capable of electrochemical reaction at the positive and negative electrodes. A representative example of such batteries is a lithium secondary battery, which stores electrical energy by the difference in chemical potential when lithium ions are intercalated / deintercalated at the positive and negative electrodes.

[0003] The lithium secondary battery is manufactured by using a material capable of reversible intercalation / deintercalation of lithium ions as a positive electrode and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Lithium composite oxides are used as the positive electrode active material of lithium secondary batteries, and examples of such composite oxides that have been researched include LiCoO2, LiMn2O4, LiNiO2, and LiMnO2.

[0005] Among the positive electrode active materials, LiCoO2 is the most widely used because of its excellent life characteristics and charge / discharge efficiency. However, it has a drawback in that it is expensive due to the limited availability of cobalt as a raw material, and therefore has limited price competitiveness.

[0006] Lithium manganese oxides such as LiMnO2 and LiMn2O4 have the advantages of being thermally safe and inexpensive, but have problems with small capacity and poor high-temperature properties. In addition, LiNiO2-based positive electrode active materials show high discharge capacity battery characteristics, but are difficult to synthesize due to the problem of cation mixing between Li and transition metals, which causes major problems in rate characteristics.

[0007] In addition, a large amount of Li by-products are generated depending on the degree of cation mixing, and most of these Li by-products consist of compounds of LiOH and Li2CO3, which causes gelation during the preparation of the positive electrode paste and gas generation during charge and discharge after the electrode is manufactured. Residual Li2CO3 not only increases the swelling phenomenon of the cell, reducing the cycle, but also causes the battery to swell.

[0008] To overcome these shortcomings, the demand for high-Ni type positive electrode active materials with Ni content of 50% or more as the positive electrode active material for secondary batteries has increased. However, although such high-Ni type positive electrode active materials show high capacity characteristics, there is a problem in that the increased Ni content in the positive electrode active material causes structural instability due to Li / Ni cation mixing. Due to the structural instability of such positive electrode active materials, lithium secondary batteries can rapidly deteriorate not only at high temperatures but also at room temperature.

[0009] Therefore, there is a need to develop a positive electrode active material that can overcome the problems associated with high-Ni positive electrode active materials. Summary of the Invention [Problem to be solved by the invention]

[0010] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles is playing a leading role in the market, while the demand for positive electrode active materials used in lithium secondary batteries is also continuously changing.

[0011] For example, lithium secondary batteries using LFP have traditionally been used primarily for reasons such as ensuring safety, but recently there has been a trend toward expanding use of nickel-based lithium composite oxides, which have a larger energy capacity per weight than LFP.

[0012] Recently, in order to realize high capacity of nickel-based lithium composite oxide, attempts to use high-Ni positive electrode active materials with increased Ni content in the lithium composite oxide have been ongoing. However, high-Ni positive electrode active materials contain excessive Li by-products and are structurally unstable, so research is being conducted to alleviate this through dopants or coatings.

[0013] The surface of the positive electrode active material is an area where side reactions with the electrolyte can occur during charging / discharging and / or storage of the lithium secondary battery, and the larger the surface area of ​​the positive electrode active material (which can be expressed as an index called BET specific surface area, for example), the higher the possibility of side reactions, and the phase transformation of the crystal structure within the surface of the positive electrode active material can occur (for example, from layered structure to rock salt structure). This phase transformation of the crystal structure within the surface of the positive electrode active material has been suggested as one of the causes of the reduced life characteristics of lithium secondary batteries.

[0014] Therefore, an object of the present invention is to provide a method for producing a positive electrode active material for a lithium secondary battery, which can improve the electrochemical properties and stability of the positive electrode active material by controlling the specific surface area of ​​the positive electrode active material.

[0015] Another object of the present invention is to provide a positive electrode including a positive electrode active material prepared by the method defined herein, and a lithium secondary battery using the positive electrode. [Means for solving the problem]

[0016] According to one aspect of the present invention, there is provided a method for preparing a positive electrode active material for a lithium secondary battery, the method including: (a) mixing a nickel composite precursor, a lithium compound, and a first additive to prepare a first mixture; (b) subjecting the first mixture to a first heat treatment to obtain a first lithium composite oxide; (c) mixing the first lithium composite oxide and the second additive to prepare a second mixture; and (d) subjecting the second mixture to a second heat treatment to obtain a second lithium composite oxide.

[0017] Here, the first additive and the second additive each independently comprise at least one selected from Al2O3, Al(OH)3, AlPO4, Al(PO3)3, WO3, Mg(OH)2, NH4F, TiO2, H3BO3, H2B4O7, B2O3, B2O5, C6H5B(OH)2, (C6H5O)3B, [(CH3(CH2)3O)3B, C3H9B3O6 and (C3H7O3)B, and the first additive and the second additive may be the same or different from each other.

[0018] In addition, the second heat treatment temperature is controlled to be lower than the first heat treatment temperature, thereby preventing the specific surface area of ​​the second lithium composite oxide obtained in step (d) from becoming excessively large.

[0019] In addition, prior to step (c), the first lithium composite oxide is reacted with a washing solution to remove the first additive remaining in the first lithium composite oxide, and then the subsequent step is performed, thereby inducing a smooth reaction between the first lithium composite oxide and the second additive, and thus enabling the specific surface area of ​​the lithium composite oxide to be controlled as intended in the present application.

[0020] The second lithium composite oxide obtained by the above preparation method may be represented by the following Chemical Formula 1.

[0021] [Chemical formula 1] Li w Ni 1-(x+y+z) Co x M1 y M2z O2

[0022] (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from Mn, B, Ba, Ce, Hf, Ta, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu; M1 and M2 are different elements, 0.5≦w≦1.5, 0≦x≦0.50, 0 <y≦0.20、0≦z≦0.20である)

[0023] According to another aspect of the present invention, there is provided a positive electrode comprising the positive electrode active material produced by the above-described production method.

[0024] According to yet another aspect of the present invention, there is provided a lithium secondary battery using the above positive electrode. Effect of the Invention

[0025] According to the present invention, in a process for preparing a positive electrode active material, a nickel composite precursor and a first additive are mixed and then subjected to a first heat treatment, thereby controlling the BET specific surface area of ​​a first lithium composite oxide obtained to be within a predetermined range for the nickel composite precursor, and the first lithium composite oxide and a second additive are mixed and then subjected to a second heat treatment, thereby controlling the BET specific surface area of ​​a second lithium composite oxide obtained to be within a predetermined range for the first lithium composite oxide. This makes it possible to prevent deterioration of the electrochemical characteristics and / or stability of the positive electrode active material even when a specific metal element is doped into the positive electrode active material or a coating layer is introduced on the surface of the positive electrode active material.

[0026] That is, according to the present invention, it is possible to ensure a sufficient amount of doping of a specific metal element in the positive electrode active material or a sufficient amount of coating on the surface of the positive electrode active material, while at the same time preventing the specific surface area of ​​the lithium composite oxide constituting the positive electrode active material from becoming unnecessarily large. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Hereinafter, a method for producing a positive electrode active material for a lithium secondary battery according to the present invention, a positive electrode including the positive electrode active material produced by the method, and a lithium secondary battery using the positive electrode will be described in more detail.

[0028] Method for producing positive electrode active material for lithium secondary battery According to one aspect of the present invention, there is provided a method for preparing a positive electrode active material for a lithium secondary battery, the method including: (a) mixing a nickel composite precursor, a lithium compound, and a first additive to prepare a first mixture; (b) subjecting the first mixture to a first heat treatment to obtain a first lithium composite oxide; (c) mixing the first lithium composite oxide and the second additive to prepare a second mixture; and (d) subjecting the second mixture to a second heat treatment to obtain a second lithium composite oxide.

[0029] The step (a) is a step of preparing a first mixture by mixing a nickel composite precursor, a lithium compound, and a first additive.

[0030] The nickel composite precursor used in step (a) is a precursor of a lithium composite oxide used as a positive electrode active material, and is a nickel composite hydroxide and / or a nickel composite oxide, and can form a lithium composite oxide by reacting with a lithium compound as a Li source material.

[0031] The nickel composite precursor may contain at least nickel and cobalt, and may further contain a metal element depending on the composition of the target lithium composite oxide.

[0032] For example, the nickel composite precursor may be a nickel-cobalt-manganese composite hydroxide or composite oxide containing nickel, cobalt, and manganese, a nickel-cobalt-aluminum composite hydroxide or composite oxide containing nickel, cobalt, and aluminum, or a nickel-cobalt-manganese-aluminum composite hydroxide or composite oxide containing nickel, cobalt, manganese, and aluminum. The nickel-cobalt-(manganese / aluminum) composite hydroxide or composite oxide may be doped with a different metal element.

[0033] The different metal elements may be at least one selected from B, Ba, Ce, Hf, Ta, Cr, F, Mg, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu.

[0034] The lithium compound capable of reacting with the nickel composite precursor to form a lithium composite oxide may be lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, etc. The lithium compound is preferably mixed in the first mixture such that the ratio (Li / Metal) of the number of lithium atoms (Li) to the total number of atoms (Metal) of metal elements other than lithium is in the range of 0.95 to 1.10.

[0035] The first additive used in step (a) may comprise at least one selected from Al2O3, Al(OH)3, AlPO4, Al(PO3)3, WO3, Mg(OH)2, NH4F, TiO2, H3BO3, H2B4O7, B2O3, B2O5, C6H5B(OH)2, (C6H5O)3B, [(CH3(CH2)3O)3B, C3H9B3O6 and (C3H7O3)B. The first additive may also be provided as a mixture of at least one selected from Al2O3, Al(OH)3, AlPO4, Al(PO3)3, WO3, Mg(OH)2NH4F and TiO2 with at least one selected from H3BO3, H2B4O7, B2O3, B2O5, C6H5B(OH)2, (C6H5O)3B, [(CH3(CH2)3O)3B, C3H9B3O6 and (C3H7O3)B.

[0036] In step (a), the first additive is preferably mixed in an amount of 0.5 to 1.0 mol % based on the nickel composite precursor. If the first additive is added in an amount of less than 0.5 mol % based on the nickel composite precursor, the specific surface area of ​​the first lithium composite oxide obtained in the first heat treatment step in step (b) described below is increased only slightly. In this case, the specific surface area of ​​the final product, the second lithium composite oxide (cathode active material), is excessively reduced, making it difficult to expect a sufficient improvement in the electrochemical properties of the cathode active material.

[0037] On the other hand, if the first additive is added in an amount exceeding 1.0 mol% based on the nickel composite precursor, the specific surface area of ​​the first lithium composite oxide obtained in the first heat treatment step (b) described below may be excessively increased, and in this case, the specific surface area of ​​the final product, the second lithium composite oxide (cathode active material), may be increased, thereby decreasing the stability of the cathode active material.

[0038] Next, in step (b), the first mixture prepared in step (a) is subjected to a primary heat treatment to obtain a first lithium composite oxide.

[0039] The first heat treatment in step (b) may be performed for 5 to 10 hours at a temperature of 600 to 800°C at a rate of 2°C per minute while maintaining an O2 atmosphere in a calcination furnace. If the temperature of the first heat treatment is less than 600°C, the calcination of the first mixture may be insufficient, and the crystal growth of the first lithium composite oxide may be insufficient. On the other hand, if the temperature of the first heat treatment is more than 800°C, the thermal decomposition of the first lithium composite oxide may occur.

[0040] The first lithium composite oxide obtained in step (b) may be represented by the following Formula 1-1.

[0041] [Chemical formula 1-1] Li w Ni 1-(x+y+z) Co x M1 y M2 z O2

[0042] (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from Mn, B, Ba, Ce, Hf, Ta, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu; M1 and M2 are different elements, 0.5≦w≦1.5, 0≦x≦0.50, 0 <y≦0.20、0≦z≦0.20である)

[0043] The composition of the first lithium composite oxide may be the same as the composition of the second lithium composite oxide described below, but may differ from it in the contents of some metal elements.

[0044] In order for the first lithium composite oxide represented by Chemical Formula 1-1 to contain a different metal element other than the metal elements contained in the nickel composite precursor, the lithium compound, and the first additive, a raw material containing the different metal element must be further mixed into the first mixture in step (a).

[0045] The different metal element other than the metal element contained in the nickel composite precursor, the lithium compound, and the first additive is doped into the crystal lattice of the first lithium composite oxide, and can contribute to stabilizing the crystal structure of the first lithium composite oxide and improving the electrochemical characteristics of the first lithium composite oxide.

[0046] The present invention also relates to a method for manufacturing a positive electrode active material for a lithium secondary battery, which can improve electrochemical characteristics and stability by controlling the specific surface area of ​​the positive electrode active material. The first lithium composite oxide obtained in step (b) has a BET specific surface area of ​​1.5 to 1.8 m2 based on the above-mentioned technical problem of the present invention. 2 It is preferable that the molecular weight be set to / g.

[0047] The BET specific surface area of ​​the first lithium composite oxide is an index calculated from the amount of nitrogen gas adsorbed at liquid nitrogen temperature using a gas adsorption specific surface area measurement device.

[0048] The BET specific surface area of ​​the first lithium composite oxide depends on the BET specific surface area of ​​the nickel composite precursor. In step (b), the BET specific surface area of ​​the first lithium composite oxide can be increased compared to that of the nickel composite precursor by the first additive in the first mixture.

[0049] Accordingly, the step (b) may be performed such that a ratio s2 / s1 of the BET specific surface area s2 of the first lithium composite oxide to the BET specific surface area s1 of the nickel composite precursor exceeds 0.098.

[0050] When the ratio s2 / s1 of the BET specific surface area s2 of the first lithium composite oxide to the BET specific surface area s1 of the nickel composite precursor is 0.098 or less, the specific surface area of ​​the second lithium composite oxide (cathode active material) which is the final product obtained through a subsequent process may be excessively small. In this case, the excessively small specific surface area of ​​the second lithium composite oxide may make it difficult for the cathode active material including the second lithium composite oxide to exhibit sufficient electrochemical properties.

[0051] On the other hand, when the ratio s2 / s1 of the BET specific surface area s2 of the first lithium composite oxide to the BET specific surface area s1 of the nickel composite precursor is 0.137 or more, the specific surface area of ​​the final product, the second lithium composite oxide, is 1.2 m or less despite the secondary heat treatment step (d) described below. 2 / g. That is, since the BET specific surface area of ​​the first lithium composite oxide obtained in step (b) is not controlled to a predetermined ratio relative to the nickel composite precursor, the BET specific surface area of ​​the second lithium composite oxide may not be within an intended range. Thus, the second lithium composite oxide having an excessively large BET specific surface area may act as a cause of reducing the stability of the positive electrode active material.

[0052] Furthermore, before performing step (c), the first lithium composite oxide obtained in step (b) may be subjected to disintegration, distribution, iron removal, and / or water washing processes.

[0053] The first lithium composite oxide obtained in step (b) is reacted with a washing solution to remove the first additive remaining in the first lithium composite oxide, and then a subsequent step is performed to induce a smooth reaction between the first lithium composite oxide and the second additive.

[0054] The water washing step is preferably performed after step (b-1) of mixing at least one metal element-containing raw material with the first lithium composite oxide and then heat-treating the mixture at a temperature in the range of 600 to 800° C. before performing step (c).

[0055] After the step (b-1), a water washing process is performed to remove the first additive and at least one metal element-containing raw material remaining on the surface of the first lithium composite oxide, thereby inducing a smooth reaction between the first lithium composite oxide and the second additive.

[0056] Even if the step (b-1) is further performed, the BET specific surface area of ​​the first lithium composite oxide is 1.5 to 1.8 m 2 It is preferable that the molecular weight be set to / g.

[0057] The metal element-containing source material used in step (b-1) may be an M1-containing source material and / or an M2-containing source material represented by Chemical Formula 1. The source material may be provided as an oxide or hydroxide containing M1 and / or M2.

[0058] The crystal lattice of the first lithium composite oxide may be doped with M1 and / or M2 by the M1-containing raw material and / or M2-containing raw material used in step (b-1), or the surface of the first lithium composite oxide may be coated with an oxide containing M1 and / or M2.

[0059] The doping and coating of M1 and / or M2 can contribute to improving the thermal stability and storage stability of the final product of the positive electrode active material, while at the same time improving the electrochemical properties of the positive electrode active material. However, the doping and coating of M1 and / or M2 can increase the BET specific surface area of ​​the first lithium composite oxide by a certain amount, which can, conversely, act as a cause of deteriorating the electrochemical properties and / or stability of the final product of the positive electrode active material.

[0060] However, according to the present invention, by ensuring a sufficient amount of doping of a specific metal element in the positive electrode active material or a sufficient amount of coating on the surface of the positive electrode active material, and at the same time preventing the specific surface area of ​​the lithium composite oxide constituting the positive electrode active material from becoming unnecessarily large, it is possible to prevent a decrease in the electrochemical characteristics and / or stability of the positive electrode active material even when the positive electrode active material is doped with a specific metal element or a coating layer is introduced on the surface of the positive electrode active material.

[0061] Next, in step (c), the stage material and a second additive are mixed to prepare a second mixture.

[0062] The second additive used in step (c) may be the same as or different from the first additive. Specifically, the second additive may include at least one selected from Al2O3, Al(OH)3, AlPO4, Al(PO3)3, WO3, Mg(OH)2, NH4F, TiO2, H3BO3, H2B4O7, B2O3, B2O5, C6H5B(OH)2, (C6H5O)3B, [(CH3(CH2)3O)3B, C3H9B3O6 and (C3H7O3)B. Preferably, at least one selected from Al2O3, Al(OH)3, H3BO3, B2O3 and B2O5 may be used as the second additive.

[0063] In step (c), the second additive is preferably mixed in an amount of 0.1 to 0.5 mol % based on the nickel composite precursor. If the second additive is added in an amount of less than 0.1 mol % based on the nickel composite precursor, the specific surface area of ​​the second lithium composite oxide obtained in the second heat treatment step (d) described below is reduced only slightly. In this case, the specific surface area of ​​the final product, the second lithium composite oxide (cathode active material), is excessively large, which may reduce the stability of the cathode active material.

[0064] On the other hand, if the second additive is added in an amount exceeding 0.5 mol% based on the nickel composite precursor, the specific surface area of ​​the second lithium composite oxide obtained in the second heat treatment step (d) described below may be excessively reduced, and in this case, the electrochemical properties of the final product, the second lithium composite oxide (cathode active material), may not be sufficiently improved.

[0065] Next, in step (d), the second mixture prepared in step (c) is subjected to a second heat treatment to obtain a final product, a second lithium composite oxide (cathode active material).

[0066] The second heat treatment in step (d) may be performed for 5 to 10 hours at a temperature of 200 to 500°C at a rate of 2°C per minute while maintaining an O2 atmosphere in a sintering furnace. If the temperature of the second heat treatment is less than 200°C, the effect of reducing the specific surface area of ​​the second lithium composite oxide is small. On the other hand, if the temperature of the second heat treatment exceeds 500°C, the specific surface area of ​​the second lithium composite oxide increases, and the stability of the final product, the positive electrode active material, may decrease.

[0067] Thus, the BET specific surface area of ​​the second lithium composite oxide obtained in step (d) is 0.8 to 1.2 m 2 / g. In this case, the ratio s3 / s2 of the BET specific surface area s3 of the second lithium composite oxide to the BET specific surface area s2 of the first lithium composite oxide is preferably 0.4 to 0.8.

[0068] When the ratio s3 / s2 of the BET specific surface area s3 of the second lithium composite oxide to the BET specific surface area s2 of the first lithium composite oxide is 0.394 or less, the specific surface area of ​​the second lithium composite oxide, which is the final product obtained in step (d), becomes too small, and it is difficult to sufficiently improve the electrochemical properties of the positive electrode active material including the second lithium composite oxide.

[0069] On the other hand, when the ratio s3 / s2 of the BET specific surface area s3 of the second lithium composite oxide to the BET specific surface area s2 of the first lithium composite oxide is 0.823 or more, the specific surface area of ​​the obtained second lithium composite oxide is reduced only slightly, and in this case, the specific surface area of ​​the final product, the second lithium composite oxide (positive electrode active material), is too large, which may reduce the stability of the positive electrode active material.

[0070] The second lithium composite oxide prepared by the above series of methods may be represented by the following Chemical Formula 1.

[0071] [Chemical formula 1] Li w Ni 1-(x+y+z) Co x M1 y M2 z O2

[0072] (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from Mn, B, Ba, Ce, Hf, Ta, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu; M1 and M2 are different elements, 0.5≦w≦1.5, 0≦x≦0.50, 0 <y≦0.20、0≦z≦0.20である)

[0073] positive electrode active material According to another aspect of the present invention, there is provided a positive electrode active material produced by the above-described production method.

[0074] The positive electrode active material is provided as a lithium composite oxide including primary particles capable of lithium intercalation / deintercalation and secondary particles formed by aggregation of the primary particles. The lithium composite oxide may be a second lithium composite oxide (hereinafter, for convenience, referred to as lithium composite oxide) produced by the above-mentioned production method.

[0075] Here, the primary particle of the lithium composite oxide means one crystal grain (grain or crystallite), and the secondary particle means an aggregate formed by agglomeration of a plurality of primary particles. The primary particle may have a rod-like, elliptical and / or irregular shape. A gap and / or a grain boundary may exist between the primary particles constituting the secondary particle.

[0076] For example, the primary particles may be separated from adjacent primary particles within the secondary particle to form internal voids. Also, the primary particles may not contact adjacent primary particles to form grain boundaries, but may contact internal voids to form a surface present within the secondary particle. The surface of the primary particles present at the outermost surface of the secondary particle that is exposed to the outside air forms the surface of the secondary particle.

[0077] Here, the average major axis length of the primary particles is within a range of 0.1 μm to 5 μm, preferably 0.1 μm to 2 μm, so that the optimal density of the positive electrode manufactured using the positive electrode active material according to various embodiments of the present invention can be realized. Also, the average particle size of the secondary particles may vary depending on the number of aggregated primary particles, and may be 1 μm to 30 μm.

[0078] The positive electrode active material may also include a coating layer that covers at least a portion of the surfaces of the primary particles (e.g., interfaces between the primary particles) and / or secondary particles formed by aggregation of the primary particles.

[0079] For example, the coating layer may be present to cover at least a portion of the exposed surface of the primary particles, particularly, the coating layer may be present to cover at least a portion of the exposed surface of the primary particles present at the outermost portion of the secondary particles.

[0080] Thus, the coating layer may exist as a layer that continuously or discontinuously coats the surfaces of the primary particles and / or the secondary particles formed by agglomeration of the primary particles. When the coating layer exists discontinuously, it may exist in the form of islands.

[0081] In some cases, the oxide may be present not only at the interfaces between the primary particles and at least a portion of the surfaces of the secondary particles, but also in internal voids formed inside the secondary particles.

[0082] The coating layer thus present can contribute to improving the physical and electrochemical properties of the positive electrode active material.

[0083] In this case, the coating layer may be in the form of a solid solution that does not form a boundary with the primary particles and / or the secondary particles formed by agglomeration of the primary particles, but this is not necessarily the case.

[0084] The coating layer may contain a boron (B)-containing oxide, that is, the coating layer can be defined as a region in which a boron-containing oxide is present.

[0085] In another embodiment, the coating layer may further include at least one oxide represented by the following Chemical Formula 2:

[0086] [Chemical formula 2] Li a M3 b O c

[0087] (wherein M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd, and 0≦a≦6, 0≦b≦8, and 2≦c≦13.)

[0088] When at least one oxide represented by Chemical Formula 2 is further present in the coating layer, the oxide may be an oxide different from the boron-containing oxide.

[0089] The oxide represented by the chemical formula 2 is an oxide of lithium and an element represented by M3, or an oxide of M3. The oxide is, for example, Li a W b O c , Li a Zr b O c , Li a Ti b O c , Li a Ni b O c , Li a Co b O c , Li a Al b O c , Co b O c , Al b O c , W b O c , Zr b O c or Ti b O c However, the above examples are merely given for the sake of convenience to facilitate understanding, and the oxide defined in the present application is not limited to the above examples.

[0090] In another embodiment, the oxide represented by Chemical Formula 2 may be an oxide in which lithium and at least two elements represented by M3 are combined, or may further include an oxide in which lithium and at least two elements represented by M3 are combined. The oxide in which lithium and at least two elements represented by M3 are combined may be, for example, Li a (W / Ti) b O c , Li a (W / Zr) b O c , Li a (W / Ti / Zr)b O c , Li a (W / Ti / B) b O c It may be, but is not necessarily limited to, this.

[0091] In this case, the boron-containing oxide may be a borate-based compound represented by the following Chemical Formula 3 or a lithium borate (LBO)-based compound, or may be a composite oxide of the compound represented by the following Chemical Formula 3 and another compound (e.g., an oxide represented by Chemical Formula 2).

[0092] [Chemical formula 3] Li a B b M4 b′ O c

[0093] (wherein M4 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd, and 0≦a≦6, 0≦b≦8, 0≦b′≦8, and 2≦c≦13.)

[0094] Non-limiting examples of the boron-containing oxide include B2O3, Li2O-B2O3, Li3BO3, Li2B4O7, Li2B2O7, and Li2BO. 13 etc.

[0095] In addition, the coating layer may be in a form in which an oxide containing boron and an oxide represented by Chemical Formula 2 are present simultaneously in one layer, or an oxide containing boron and an oxide represented by Chemical Formula 2 are present in separate layers.

[0096] For example, the coating layer may include a first oxide layer including at least one oxide represented by Chemical Formula 2 and a second oxide layer including a boron-containing oxide.

[0097] In this case, the first oxide layer may be present so as to cover at least a part of the exposed surface of the primary particle (i.e., the surface of the secondary particle) present at the outermost part of the secondary particle, and the second oxide layer may be present so as to cover at least a part of the exposed surface of the primary particle not covered by the first oxide layer and the surface of the first oxide layer.

[0098] In particular, the second oxide layer is present so as not to entirely cover the exposed surfaces of the primary particles not covered by the first oxide layer and the surface of the first oxide layer, thereby improving the efficiency of lithium ion conduction.

[0099] As described above, the lithium composite oxide according to the present embodiment includes a coating layer that covers at least a portion of the surface of the primary particles (e.g., interfaces between the primary particles) and / or secondary particles formed by agglomeration of the primary particles, thereby enhancing structural stability. In addition, the lithium composite oxide can be used as a positive electrode active material for a lithium secondary battery to improve its lifespan and capacity characteristics.

[0100] In addition, the coating layer reduces residual lithium in the lithium composite oxide and acts as a diffusion path for lithium ions, thereby improving the efficiency characteristics of the lithium secondary battery.

[0101] Furthermore, the oxide may exhibit a concentration gradient that decreases from the surface portion of the secondary particle toward the center portion of the secondary particle, whereby the concentration of the oxide may decrease from the outermost surface of the secondary particle toward the center portion of the secondary particle.

[0102] As described above, the oxide exhibits a concentration gradient that decreases from the surface portion of the secondary particle toward the center portion of the secondary particle, thereby effectively reducing residual lithium present on the surface of the positive electrode active material, and thus preventing side reactions due to unreacted residual lithium. In addition, the oxide can prevent the crystallinity of the surface inner region of the positive electrode active material from decreasing. In addition, the oxide can prevent the overall structure of the positive electrode active material from collapsing during an electrochemical reaction.

[0103] Lithium secondary battery According to yet another aspect of the present invention, there is provided a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer may include a positive electrode active material prepared by the method according to any of the various embodiments of the present invention as a positive electrode active material.

[0104] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0105] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.

[0106] At this time, the positive electrode active material may be included in an amount of 80 to 99 wt%, more specifically, 85 to 98.5 wt%, based on the total weight of the positive electrode active material layer. When included in this content range, excellent capacity characteristics can be exhibited, but the amount is not necessarily limited thereto.

[0107] The conductive material is used to impart electrical conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0108] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be included in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0109] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.

[0110] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.

[0111] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.

[0112] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0113] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.

[0114] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0115] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0116] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0117] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.

[0118] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide, or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, may be used. A metallic lithium thin film may be used as the negative electrode active material. Low-crystalline carbon and high-crystalline carbon may both be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0119] The negative electrode active material may be included in an amount of 80 to 99 wt % based on the total weight of the negative electrode active material layer.

[0120] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of usually 0.1 to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0121] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskey such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.

[0122] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0123] In another embodiment, the negative electrode active material layer may be manufactured by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0124] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, in order to ensure heat resistance or mechanical strength, a separator coated with a ceramic component or a polymer material may be used, and may be selectively used as a single-layer or multi-layer structure.

[0125] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0126] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0127] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.

[0128] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3), LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably used within a range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that excellent electrolyte performance can be exhibited and lithium ions can be effectively transferred.

[0129] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5% by weight based on the total weight of the electrolyte.

[0130] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0131] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.

[0132] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.

[0133] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.

[0134] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.

[0135] Production Example 1. Production of positive electrode active material (1) Example 1 Spherical Ni particles were prepared by the co-precipitation method. 0.80 Co 0.12 Mn 0.08The (OH)2 hydroxide precursor was synthesized. Specifically, 25 wt% NaOH and 30 wt% NH4OH were added to a 1.5M composite transition metal sulfate aqueous solution, which was a mixture of nickel sulfate, cobalt sulfate, and manganese sulfate in a molar ratio of 80:12:8, in a 90L reactor. The pH in the reactor was maintained at 11.5, the temperature of the reactor was maintained at 60°C, and inert gas N2 was added to the reactor to prevent the precursor from being oxidized. After the synthesis and stirring were completed, the precursor was washed and dehydrated using a filter press (F / P) equipment, and Ni 0.80 Co 0.12 Mn 0.08 (OH)2 hydroxide precursor (nickel composite precursor) was obtained.

[0136] Next, the nickel composite precursor was mixed with LiOH (Li / (Ni+Co+Mn) molar ratio=1.01) as a lithium compound and 0.5 mol% of a first additive (H3BO3) relative to the nickel composite precursor, and then the mixture was heated to 700°C at a rate of 2°C per minute while maintaining an O2 atmosphere in a sintering furnace, and heat-treated for 12 hours. Then, the mixture was crushed to obtain a first lithium composite oxide.

[0137] The first lithium composite oxide was mixed with 0.15 mol % Al2O3 and 0.3 mol % TiO2 relative to the first lithium composite oxide, and then further heat-treated for 8 hours by increasing the temperature to 680°C at a rate of 2°C per minute while maintaining an O2 atmosphere in a sintering furnace.

[0138] Next, the first lithium composite oxide was mixed with distilled water, and then washed with water for 30 minutes. The washed first lithium composite oxide was filtered and then dried.

[0139] The dried first lithium composite oxide was mixed with a second additive (H3BO3) of 0.15 mol% based on the first lithium composite oxide, and then the mixture was heated to 300°C at a rate of 2°C per minute while maintaining an O2 atmosphere in a sintering furnace, and heat-treated for 8 hours to obtain a second lithium composite oxide.

[0140] (2) Example 2 A positive electrode active material was prepared in the same manner as in Example 1, except that the first additive (H3BO3) was mixed in an amount of 1.0 mol % based on the nickel composite precursor.

[0141] (3) Example 3 A positive electrode active material was prepared in the same manner as in Example 1, except that Al2O3 was mixed to be 0.5 mol% based on the first lithium composite oxide, and the second additive (H3BO3) was mixed to be 0.5 mol% based on the first lithium composite oxide.

[0142] (4) Example 4 A positive electrode active material was prepared in the same manner as in Example 1, except that TiO2 was mixed to be 0.5 mol % relative to the first lithium composite oxide.

[0143] (5) Example 5 A positive electrode active material was prepared in the same manner as in Example 1, except that after mixing Al2O3 and TiO2 with the first lithium composite oxide, no additional heat treatment was performed.

[0144] (6) Comparative Example 1 A positive electrode active material was prepared in the same manner as in Example 1, except that the dried first lithium composite oxide was heat-treated without mixing the second additive (H3BO3).

[0145] (7) Comparative Example 2 A positive electrode active material was prepared in the same manner as in Example 1, except that the nickel composite precursor was heat-treated without mixing the first additive (H3BO3).

[0146] (8) Comparative Example 3 A positive electrode active material was prepared in the same manner as in Example 1, except that the first additive (H3BO3) was mixed in an amount of 1.25 mol % based on the nickel composite precursor.

[0147] (9) Comparative Example 4 A positive electrode active material was prepared in the same manner as in Example 1, except that the first additive (H3BO3) was mixed in an amount of 0.25 mol % based on the nickel composite precursor.

[0148] (10) Comparative Example 5 A positive electrode active material was prepared in the same manner as in Example 1, except that the second additive (H3BO3) was mixed in an amount of 1.0 mol % based on the first lithium composite oxide.

[0149] (11) Comparative Example 6 A positive active material was prepared in the same manner as in Example 1, except that the second additive (H3BO3) was mixed with the dried first lithium composite oxide and then no additional heat treatment was performed.

[0150] Manufacturing Example 2. Manufacturing of lithium secondary batteries A positive electrode slurry was prepared by dispersing 92 wt% of the positive electrode active material prepared in Preparation Example 1, 4 wt% of artificial graphite, and 4 wt% of PVDF binder in 30 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly applied to a thin aluminum film having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0151] A coin battery was fabricated using a lithium foil as a counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) as a separator, and an electrolyte of LiPF6 at a concentration of 1.15 M in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7.

[0152] Experimental Example 1. BET Measurement of Nickel Composite Precursor and Lithium Composite Oxide During the process of producing a positive electrode active material by Production Example 1, a nickel composite precursor, a first lithium composite oxide, and a second lithium composite oxide were obtained and their BET specific surface areas were measured. The BET specific surface areas were calculated from the amount of nitrogen gas adsorbed at liquid nitrogen temperature (77 K) using a gas adsorption specific surface area measurement device (MicrotracBEL, BELSORP-mini II).

[0153] The measurement results of the BET specific surface area are shown in Table 1 below.

[0154] [Table 1]

[0155] Experimental Example 2: Evaluation of the electrochemical properties of lithium secondary batteries A charge-discharge experiment was carried out on the lithium secondary battery (coin cell) manufactured in Manufacturing Example 2 using an electrochemical analyzer (Toyo, Toscat-3100) at 25° C., voltage range of 3.0 V to 4.3 V, and discharge rate of 0.1 C, to measure the charge and discharge capacities.

[0156] In addition, the same lithium secondary battery was charged and discharged 50 times at 25°C and within a driving voltage range of 3.0 V to 4.4 V at 1 C / 1 C, and then the ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention) was measured.

[0157] The measurement results are shown in Table 2 below.

[0158] [Table 2]

[0159] Although the embodiments of the present invention have been described above, a person having ordinary knowledge in the art may modify and change the present invention in various ways by adding, changing, deleting or adding elements without departing from the concept of the present invention described in the claims, and this may also be said to be within the scope of the claims of the present invention.

Claims

1. Lithium composite oxide capable of lithium intercalation / deintercalation, A first oxide layer covering at least a part of the surface of the lithium composite oxide; and a second oxide layer covering a surface of the first oxide layer and at least a portion of a surface of the lithium composite oxide that is not covered by the first oxide layer; Including, The first oxide layer and the second oxide layer contain a boron-containing oxide represented by the following Chemical Formula 3: The lithium composite oxide is a positive electrode active material represented by the following chemical formula 1. [Chemical formula 3] Li a B b M4 b’ O c (Here, M4 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd, and 0≦a≦6, 0<b≦8, 0≦b′≦8, and 2≦c≦13.) [Chemical Formula 1] Li w Ni 1-(x+y+z) Co x M1 y M2 z O 2 (Here, M1 is at least one selected from Mn and Al, M2 is at least one selected from Mn, B, Ba, Ce, Hf, Ta, Cr, F, Mg, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu, M1 and M2 are different elements, and 0.5≦w≦1.5, 0≦x≦0.50, 0<y≦0.20, 0≦z≦0.20, and 0<x+y+z≦0.50.)

2. The first oxide layer is a hydroxide precursor of the lithium composite oxide, a lithium compound, and H 3 B.O. 3 , H 2 B 4 O 7 , B 2 O 3 , B 2 O 5 , C 6 H 5 B(OH) 2 , (C 6 H 5 O) 3 B, [(CH 3 (CH 2 ) 3 O) 3 B, C 3 H 9 B 3 O 6 and (C 3 H 7 O 3 2. The positive electrode active material according to claim 1, which is formed by heat-treating a first mixture having a first additive containing at least one selected from the group consisting of:

3. The first oxide layer is composed of a hydroxide precursor of the lithium composite oxide, a lithium compound, and Al 2 O 3 , Al(OH) 3 , AlPO 4 , Al(PO 3 ) 3 , W.O. 3 , Mg(OH) 2 , N.H. 4 F and TiO 2 At least one selected from and H 3 B.O. 3 , H 2 B 4 O 7 , B 2 O 3 , B 2 O 5 , C 6 H 5 B(OH) 2 , (C 6 H 5 O) 3 B, [(CH 3 (CH 2 ) 3 O) 3 B, C 3 H 9 B 3 O 6 and (C 3 H 7 O 3 2. The positive electrode active material according to claim 1, which is formed by heat-treating a first mixture having a first additive containing at least one selected from the group consisting of:

4. The positive electrode active material of claim 3 , wherein the first oxide layer further comprises a metal oxide represented by the following Chemical Formula 2: [Chemical formula 2] Li a M3 b O c (Here, M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd, 0≦a≦6, 0≦b≦8, 2≦c≦13, and a and b are not 0 at the same time.)

5. When a lithium composite oxide having only the first oxide layer formed on a surface thereof is defined as a first lithium composite oxide, and a lithium composite oxide having the second oxide layer formed on a surface of the first lithium composite oxide is defined as a second lithium composite oxide, The second oxide layer is made of the first lithium composite oxide and H 3 B.O. 3 , H 2 B 4 O 7 , B 2 O 3 , B 2 O 5 , C 6 H 5 B(OH) 2 , (C 6 H 5 O) 3 B, [(CH 3 (CH 2 ) 3 O) 3 B, C 3 H 9 B 3 O 6 and (C 3 H 7 O 3 2. The positive electrode active material according to claim 1, which is formed by heat-treating a second mixture having mixed therein a second additive containing at least one selected from the group consisting of:

6. When a lithium composite oxide having only the first oxide layer formed on a surface thereof is defined as a first lithium composite oxide, and a lithium composite oxide having the second oxide layer formed on a surface of the first lithium composite oxide is defined as a second lithium composite oxide, The second oxide layer is made of the first lithium composite oxide, a lithium compound, and Al. 2 O 3 , Al(OH) 3 , AlPO 4 , Al(PO 3 ) 3 , W.O. 3 , Mg(OH) 2 , N.H. 4 F and TiO 2 At least one selected from and H 3 B.O. 3 , H 2 B 4 O 7 , B 2 O 3 , B 2 O 5 , C 6 H 5 B(OH) 2 , (C 6 H 5 O) 3 B, [(CH 3 (CH 2 ) 3 O) 3 B, C 3 H 9 B 3 O 6 and (C 3 H 7 O 3 2. The positive electrode active material according to claim 1, which is formed by heat-treating a second mixture having mixed therein a second additive containing at least one selected from the group consisting of:

7. The second additive is Al 2 O 3 and Al(OH) 3 At least one selected from and H 3 B.O. 3 , B 2 O 3 and B 2 O 5 The positive electrode active material according to claim 6 , comprising at least one selected from the following:

8. The positive electrode active material of claim 6 , wherein the second oxide layer further comprises a metal oxide represented by the following Chemical Formula 2: [Chemical formula 2] Li a M3 b O c (Here, M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd, 0≦a≦6, 0≦b≦8, 2≦c≦13, and a and b are not 0 at the same time.)

9. 6. The positive electrode active material according to claim 5, wherein a ratio (mol ratio) of a content (mol %) of boron derived from the first oxide layer to a total content (mol %) of metal elements excluding lithium in the first lithium composite oxide is 0.5 to 1.

0.

10. 6. The positive electrode active material according to claim 5, wherein a ratio (mol ratio) of a content (mol %) of boron derived from the second oxide layer to a total content (mol %) of metal elements excluding lithium in the second lithium composite oxide is 0.1 to 0.

5.

11. Before forming the second oxide layer on the surface of the first lithium composite oxide, the first lithium composite oxide has a BET specific surface area of ​​1.5 to 1.8 m 2 The positive electrode active material according to claim 5 , wherein the Mo content is 1 / g.

12. The BET specific surface area measured from the second lithium composite oxide is 0.8 to 1.2 m 2 The positive electrode active material according to claim 5 , wherein the Mo content is 1 / g.

13. 6. The positive electrode active material according to claim 5, wherein a ratio of a BET specific surface area of ​​the second lithium composite oxide to that of the first lithium composite oxide is greater than 0.394 and less than 0.

823.

14. The positive electrode active material according to claim 1 , wherein a metal oxide represented by the following chemical formula 2 is present between the first oxide layer and the second oxide layer: [Chemical formula 2] Li a M3 b O c (Here, M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd, 0≦a≦6, 0≦b≦8, 2≦c≦13, and a and b are not 0 at the same time.)

15. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 14.

16. A lithium secondary battery using the positive electrode according to claim 15.

Citation Information

Patent Citations

  • Positive electrode active material for lithium secondary battery, method for producing same, and lithium secondary battery including the same

    JP2018500720A

  • Method for producing positive electrode active material for lithium secondary battery

    JP2023542856A

  • Lithium secondary battery positive electrode active material, method for preparing same, and lithium secondary battery positive electrode and lithium secondary battery comprising same

    WO2019078689A2